Estimating rotational FRFs of a complex structure using FE model updating, mode expansion and FRF synthesis method - W. I. I., Wan Iskandar Mirza; M. N., Abdul Rani; M. A., Yunus; Rina, Febrina; M. S. M., Sani (IOP Publishing, 2020)
Estimating rotational frequency response functions (FRFs) from experimental data is very challenging, and the estimation often leads to poor FRFs due to the presence of spurious resonance peaks. In practice, special equipment is essentially required in the measurement process, unless the rotational FRFs are synthesised using measured modal data. This paper presents an alternative approach for estimating the rotational FRFs of a geometrically complex structure by using finite element modal updating, mode expansion and the FRF synthesis method. The applicability and accuracy of the proposed approach are demonstrated on a car front-end module A simplified finite element (SFE) model of the test structure is introduced and the SFE model is then updated based on the measured modal model obtained from experimental modal analysis. The mode shapes of the updated SFE model are expanded to the test model to obtain the entire translational and rotational modal vector. The rotational FRFs of the expended experimental model is derived via the FRF synthesis method. The derived translational FRF is compared with the measured counterparts for validation purposes. It was found that the derived translational and measured FRF are in a perfect match, and the derived rotational FRF has successfully estimated all the resonance peaks within the frequency of interest. The findings from this work may be useful in improving the accuracy of the experimental rotational FRFs, which are crucial for particular structural dynamics analysis.